Marital Satisfaction and Social Media Use: A Comparative Study Based On Addiction Levels - Ayhan, Fatma; Arık, Elif; SAÇAN, Merve Gülsüm; Sevim, Zehra; Arguç, Esme (Makara Human Behavior Studies in Asia, 2026)
In recent years, the widespread use of social media platforms has raised questions about their impact on marital relationships. This study examined the relationship between marital satisfaction, social media use, and certain sociodemographic characteristics. This descriptive and cross-sectional study comprised 461 individuals residing in Turkey who had been married for at least one year. Data were collected using the Bergen Social Media Addiction and Marital Satisfaction Scales. Statistical analyses included t-tests, analysis of variance, and multiple linear regression analysis. Social media addiction was high among 16.5% of the participants. Marital satisfaction was higher among males, those who married at age 25 or older, individuals in their first five years of marriage, those with fewer children, those with regular employment and higher income, and those who made their own decision to marry. Regression analysis revealed that age, gender, social media addiction score, and autonomy in the marriage decision were significant marital satisfaction predictors. Social media addiction is negatively associated with marital satisfaction. In addition, factors such as personal autonomy in the marriage decision, age, and gender significantly predict marital satisfaction. These findings indicate that when planning preventive and supportive interventions to enhance marital satisfaction, these variables should be considered.